Growth Performance Of F3 Hybrid Local Chickens Fed With Fermented Feed Containing Probiotics And Digestive Enzymes - Alkautsar -; Muhammad Aman Yaman; Wenny Ladhunka Nur Aliyya; Riski Ambia Rahman; Dessi Astika; Sarini Sri Utari; Putri Nadia Riana (Jurnal Ternak, 2026)
This study aims to evaluate the effectiveness of using fermented feed containing local probiotics and digestive enzymes on the growth of hybrid local chickens during the grower phase, which has been carried out at the Livestock Field Laboratory (LLP) of the Department of Animal Husbandry, Syiah Kuala University, Teuku Umar University Livestock Physiology and Reproduction Laboratory, and Plant Disease Laboratory, Faculty of Agriculture, Syiah Kuala University, Banda Aceh. The research material consisted of 150 Day Old Chicken (DOC) F3 hybrid local chickens derived from ALPU KUB cross, which were grouped by sex and given four different treatments, namely: (P0) 100% commercial feed, (P1) 100% fermented feed of local probiotics and digestive enzymes, (P2) a mixture of 50% fermented local probiotics and digestive enzymes with 50% commercial feed, and (P3) a mixture of 30% fermented local probiotics and digestive enzymes with 70% commercial feed. The results showed that fermented feed had a significant effect (P<0.05) on the weight gain of chickens from 5 to 20 weeks of age, both males and females, with an increase in feed conversion and efficiency, while 100% fermentation caused a decrease in feed consumption, conversion, and efficiency which had an impact on the growth of hybrid local chickens during the grower phase. In the future, this research is expected to serve as a foundation for developing more efficient and sustainable fermented feed technology, while also enhancing the productivity of local hybrid chickens.